A literary approach to the human rights discourse: the case of Zimbabwean literature - Javangwe, Tasiyana D.; Tagwirei, Cuthbeth (Midlands State University, 2015)
The article explores the interface between human rights and Zimbabwean literature. It discusses the possibility of demystifying the notion of human rights by making human rights discourse accessible to ordinary people through literary works. The argument stems from the realization that human rights discourse is couched in unusual terms and expressions which makes it a privileged discourse from which various individuals are alienated. This is unfortunate in the sense that human rights are universal and they emerge within culturally specific contexts. An understanding of specific literary works is therefore crucial to an understanding of a society’s grasp and mediation of human rights issues. Through a re-reading of selected Zimbabwean literary works, the researchers argue for the need to make human rights discourse more accessible through literature. In this endeavor, literary works are seen to play a pivotal role in addressing human rights concerns by familiarizing the reader with those values sections of Zimbabwean society consider valuable and pointing out incidents of human rights abuses. The researchers note that human rights are values that are distinct to all societies and so is art in general. The relationship between the two needs to be explored for a better recognition of the rights of all people.